Performance Pay, Competitiveness, and the Gender Wage Gap: Evidence from the United States - Andrew McGee; Peter McGee; Jessica Pan (Institute for the Study of Labor (IZA), 2014)
Evidence that women are less likely to opt into competitive compensation schemes in the laboratory has generated speculation that a gender difference in competitiveness contributes to the gender wage gap. Using data from the NLSY79 and NLSY97, we show that women are less likely to be employed in jobs using competitive compensation. The portion of the gender wage gap explained by gender segregation in compensation schemes is small in the NLSY79 but somewhat larger in the NLSY97 suggesting an increasing role for competitiveness in explaining the gender wage gap.
Keywords: J16; A12; 330; gender wage gap; competitiveness; performance pay